Critical graphs with respect to vertex identification - Frick, Marietjie; Fricke, Gerd H.; Mynhardt, Christina M.; Skaggs, R. Duane (Utilitas Mathematica, 2008)
We explore various types of criticality with respect to differentiating-dominating sets, or identifying codes. Existence and characterization results are included. We conclude with open problems.